Dynamics and drivers of the carbonate system: response to terrestrial runoff and upwelling along the Northeastern Colombian Caribbean coast - Ricaurte-Villota, Constanza; Murcia-Riaño, Magnolia; Hernádez-Ayón, José Martín (Frontiers in Marine Science, 2025)
IntroductionThis study investigated the variability and main drivers of the carbonate system in Gayraca Bay and Chengue Bay, located on the northeastern Caribbean coast of Colombia, through monthly measurements of partial pressure of CO2 (pCO2), pH, total alkalinity (TA), and dissolved inorganic carbon (DIC) from 2017 to 2022. Statistical analyses and Taylor series decomposition were employed to determine the seasonal and interannual contributions of sea surface temperature, salinity, TA, and DIC to changes in pCO2, pH, and calcium carbonate saturation state (Ω).ResultsThe results showed significant seasonal variability influenced by annual changes in coastal upwelling, rainfall, and river runoff. Low/high pH and Ω values were associated with high/low DIC and TA values during the dry and wet seasons, respectively, while pCO2 exhibited an opposite pattern. During El Niño, negative anomalies in coastal upwelling produced negative anomalies in pCO2 and positive anomalies in Ω, DIC, and TA. Conversely, during La Niña, alternating periods of positive rainfall and upwelling anomalies were observed. Higher rainfall corresponded to negative anomalies in pCO2, DIC, and TA and positive anomalies in Ω, whereas stronger upwelling led to opposite trends. In early 2022, undersaturated levels of Ωcalc and Ωarag (<1) were observed, which could affect coral calcification and pose risks in future climate change scenarios. Taylor series decomposition analysis identified TA and DIC as primary drivers of carbonate system variability, modulated by seasonal and interannual changes in rainfall and river runoff, which are influenced by ENSO events. The observed trends in pH and pCO2 were driven by a decrease in DIC and TA, attributed to increased river runoff, contrasting with typical ocean acidification trends driven by rising atmospheric CO2 levels.DiscussionThis highlights the region's unique dynamics and underscores the importance of local studies. This study provides a novel 6-year time-series dataset for the carbonate system in the Colombian Caribbean, offering a valuable baseline for assessing the impacts of global warming and ocean acidification in the region.